A Systematic Review of the Outcomes, Level, Facilitators, and Barriers to Deep Self-Reflection in Public Health Higher Education: Meta-Analysis and Meta-Synthesis - Lim, Raymond Boon Tar; Hoe, Kenneth Wee Beng; Zheng, Huili (Frontiers in Education, 2022)
Based on 34 studies and to the best of our knowledge, this is the first systematic review consisting of a meta-analysis and a meta-synthesis to illustrate the various self-reflection formats used in public health higher education. Through this review, we aimed to (1) describe the range of self-reflection formats used in public health undergraduate education, (2) compare the level of reflectivity and outcomes of self-reflection according to the common formats of self-reflection used, and (3) compare the facilitators and barriers to deep self-reflection based on the common formats of self-reflection used. Most students were not engaging in reflection at a deep level according to the Mezirow's model of reflexivity. Both meta-analysis and meta-synthesis results revealed self-reflection enhanced self-confidence, professional identity, and professional development as well as improved understanding of public health related topics in these students. Future educational programmes should consider the common facilitators to deep self-reflection, i.e., advocacy on the importance of reflection by instructors and provision of guidance to students and the common barriers, i.e., perception by instructors/students to be time consuming and the imbalance in power relationship between instructors and students. Because perceptions of learning environments varied between institutions, programs, teachers and students, efforts to evaluate the implementation feasibility of these facilitators and barriers need to take place across the different levels. As a start, peer ambassadors or champions could be appointed at the student level to change the common perception that performing deep self-reflection was time consuming. Similarly, at the teacher level, faculty learning communities could be set up for like-minded educators to advocate on the importance of reflection and to share their experience on balancing the power relationship between instructors and students. Systematic Review Registration: PROSPERO, identifier: CRD42021255714.